VD_FINDINFO HC / 2016 / 334 vom 20. April 2016 - VD Tribunal cantonal (2016)
MESURE PROVISIONNELLE, CRÉANCE, SOCIÉTÉ SIMPLE, LIQUIDATIONEN GÉNÉRAL | 101 al. 1 ch. 1 CPC, 108 al. 3 CPC, 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)